Reconstruction by bone transport after resection of benign tumors of tibia: A retrospective study of 38 patients - Borzunov, Dmitry Y (Indian J Orthop, 2015)
BACKGROUND: The commonly used reconstructive options after post resection defects in bone tumors like megaprosthesis, autograft, allograft, bone graft substitutes and recycled bone have their own demerits on a long term. Bone transport that regenerates patient's own bone is a less explored option of reconstruction after resection of benign bone tumors and reports on this are limited. This technique is very much relevant in tibia where Ilizarov fixator is surgeon and patient friendly. We report our experience. MATERIALS AND METHODS: This is a retrospective series of resection and bone transport in 38 patients with benign tumor of tibia. There were 14 males and 24 females with mean age of 23.40 years (range 9–40 years). Lesion was located in proximal third tibia in 27, middle third in two and distal third in nine patients. The diagnosis was giant cell tumor in 32, chondroblastoma in three, chondromyxoid fibroma, enchondroma and desmoplasic fibroma in one patient each. The resection was intercalary in 28 and transarticular in 10 patients. Osteosynthesis was monofocal in three, bifocal in 31 and polyfocal in four cases. RESULTS: Mean followup was 7.22 years (range 1.5–15 years). Mean resection length was 10.21 cm (range 3–22 cm). The mean duration of external fixator was 308.03 days (range 89–677 days) and mean external fixator index was 36.14 days/cm (range 16.84–97.43 days/cm). Twelve patients had difficulties in the form of 11 problems and five obstacles that were successfully managed. None of the patients had local recurrence of tumor or any long term complication. Mean Musculo-skeletal Tumour Society score at final followup was 27.18 (90.60%). CONCLUSIONS: Bone transport is an excellent option after resection of benign tumors of tibia with good local control and functional outcome, despite minor difficulties that need timely management.